The Patriarchal Construction and Its Impact on Personal Identity in Virginia Woolf Mrs Dalloway - Eka Gunadharma Sakti; Prayudias Margawati (Journal of Creative Student Research, 2026)
This study examines the influence of structural patriarchy on personal identity formation and psychological distress in Virginia Woolf’s Mrs. Dalloway through the character of Septimus Warren Smith. Employing a descriptive qualitative method, the research analyzes narrative passages, dialogues, and character experiences using Sylvia Walby’s theory of structural patriarchy. The findings reveal that patriarchal structures operate through interconnected cultural and institutional mechanisms that regulate masculinity and suppress emotional vulnerability. Septimus internalizes dominant masculine ideals that equate strength with emotional restraint, leading him to repress grief and trauma following his wartime experiences. His psychological suffering is further intensified by medical authorities, particularly Dr. Holmes and Sir William Bradshaw, whose concepts of Proportion and Conversion function as instruments of social conformity rather than genuine care. These institutional interventions marginalize Septimus’s experiences, diminish his personal agency, and accelerate the fragmentation of his identity. Ultimately, his suicide emerges as the tragic consequence of a prolonged conflict between individual subjectivity and patriarchal power. The study concludes that Woolf critiques a social system that prioritizes conformity, productivity, and masculine ideals over empathy and psychological well-being, demonstrating how patriarchy can adversely affect both women and men.